Otonomi Wanita: Sejumlah Studi Kasus di Jakarta - Tapi Omas Ihromi (Antropologi Indonesia, 1992)
The writer put forward that in mainstream social sciences not much attention is given to problems related to power relationship in small social units such as the family. Thus in this article attempts are made to describe how much autonomy women have regarding household economy matters. The description of cases is based on research conducted in Jakarta by the team of "Srikandi Foundation" a small research institute of which writer is one of the chairpersons.